2021
DOI: 10.5194/amt-2021-333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Smoke and Sulfuric Acid Aerosol in SAGE III/ISS Extinction Spectra Following the 2019 Raikoke Eruption

Abstract: Abstract. The 2019 eruption of Raikoke was the largest volcanic eruption since 2011 and it was coincident with 2 major wildfires in the northern hemisphere. The impact of these events was manifest in the SAGE III/ISS extinction coefficient measurements. As the volcanic aerosol layers moved southward, a secondary peak emerged at an altitude higher than that which is expected for sulfuric acid aerosol. It was hypothesized that this secondary plume may contain a non-negligible amount of smoke contribution. We dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the Raikoke southern branch at low latitudes, Knepp et al (2021) use SAGE III aerosol measurements (9 data points at near-infrared, visible, and ultraviolet wavelengths) to classify many aerosols above 20 km as smoke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Raikoke southern branch at low latitudes, Knepp et al (2021) use SAGE III aerosol measurements (9 data points at near-infrared, visible, and ultraviolet wavelengths) to classify many aerosols above 20 km as smoke.…”
Section: Discussionmentioning
confidence: 99%
“…In the Raikoke southern branch at low latitudes, Knepp et al. (2021) use SAGE III aerosol measurements (9 data points at near‐infrared, visible, and ultraviolet wavelengths) to classify many aerosols above 20 km as smoke. Absorption by black carbon in smoke particles was proposed to explain self‐lofting observed in the aerosols, behavior taken as proof of the presence of smoke.…”
Section: Discussionmentioning
confidence: 99%
“…For SAGE III/ISS aerosol extinction, we have an advantage of additional wavelength measurements including a longer wavelength (1544 nm) that can be used for the analyses. As noted above, while SAGE III/ISS measurements have been used in many studies, due to a reported negative bias in the 525 nm channel (Wang et al, 2020), we now apply a simple correction by spectrally interpolating extinction between 450 and 756 nm channel using Ångström exponent (Knepp et al, 2021). While the most commonly used wavelength combinations for SAGE series of measurements are 525 and 1020 nm, due to the reasons listed in section 2.1, we prefer to use a different wavelength combination of 756 and 1544.…”
Section: Perturbed Stratosphere and New Methodmentioning
confidence: 99%